Holmium-YAG laser for gall stone fragmentation: an endoscopic tool. Issue 3 (March 1995) - Blomley, M J; Nicholson, D A; Bartal, G; Foster, C; Bradley, A; Myers, M; Man, W; Li, S; Banks, L M
Abstract : A systematic review of the 2.1 mu holmium-YAG laser for gall stone lithotripsy was undertaken. This infrared laser, which can be used endoscopically and percutaneously, has safety advantages over other lasers and has potential as a general purpose vascular and surgical tool. Twenty nine gall stones (mean mass 1.3 g) were fragmented in vitro using pulse energies of 114 to 159 mJ/pulse at 5 Hz with a 0.6 mm fibre, while being held in an endoscopy basket. All stones were successfully fragmented, requiring an average of 566 pulses with a 5 Hz pulse repetition frequency. The number of pulses required increased with gall stone size and mass (p < 0.01), and decreased with both pulse energy (p < 0.01) and operator experience (p < 0.05). The biochemical content of the stone did not significantly affect the number of pulses needed. The potential hazard of the laser to the biliary endothelium was investigated. At the pulse energies used, five pulses at close contact penetrated into the serosa of fresh gall bladder wall. No damage was seen when two pulses were fired. This laser shows considerable promise in gall stone lithotripsy. Until further safety data are available, however, its use with endoscopic vision is advised.